1995
DOI: 10.1159/000188648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Colchicine on Schistosoma-lnduced Renal Amyloidosis in Syrian Golden Hamsters

Abstract: Seventy Syrian golden hamsters were infected with Schistosoma haematobium, and 10 uninfected hamsters served as negative controls. Of the schistosome-infected hamsters, 10 served as positive controls (infected but untreated) and the rest (60 hamsters) received treatment. In 30 hamsters treatment was given 9 weeks after infection (before the appearance of renal amyloidosis) and in the other 30 it was given after the appearance of amyloid deposits, 15 weeks after infection. Each treatment group was subdivided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Favari et al [25]and Kershenobich et al [26]reported that a number of liver injuries can be improved by colchicine intervention. In the kidney, colchicine has been shown to prevent various renal injuries, including amyloidosis with proteinuria [27], renal scarring postbacterial infection [28], antiglomerular basement membrane nephritis [29]and chronic CsA nephrotoxicity [30]. However, its modes of action have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Favari et al [25]and Kershenobich et al [26]reported that a number of liver injuries can be improved by colchicine intervention. In the kidney, colchicine has been shown to prevent various renal injuries, including amyloidosis with proteinuria [27], renal scarring postbacterial infection [28], antiglomerular basement membrane nephritis [29]and chronic CsA nephrotoxicity [30]. However, its modes of action have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Colchicine has been recently reported to prevent amyloidosis secondary to familial Mediterranean fever in humans [15] and amyloidosis secondary to Schistosoma infection in hamsters [5]. More specific to our target is that colchicine has been reported to suppress renal scarring in E. coli infected rats [6] and to be effective in preventing the acute progression of renal insufficiency and tubulointerstitial fibrosis in an experimental model of glomerulonephritis in the rabbit [8].…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine, which is an old drug used essentially for the alleviation of pain in acute gout and to suppress attacks of familial Mediterranean fever, has been recently reported to prevent schistosoma-related amyloidosis in Syrian golden hamsters [5] and renal scarring induced in rats by Escherichia coli pyelonephritis [6]. In addition, colchicine has been used with some success in the management of experimental and clinical hepatic fibrosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Amyloidosis occurs with prolonged active infection with either S. hematobium or S. mansoni in humans, as it does in several animal models [33]. Like other inflammation-associated amyloids, AA beta-pleated fibrils are deposited preferentially in the kidney, liver, subcutaneous fat, and gums.…”
Section: Clinicopathologic Interactionmentioning
confidence: 99%
“…The kidneys are shrunken in 25% of patients, in whom there is associated schistosomal interstitial fibrosis. No evidence indicates that the course of schistosoma-associated amyloidosis can be modified by any form of treatment [33].…”
Section: Clinicopathologic Interactionmentioning
confidence: 99%